2016
DOI: 10.3892/br.2016.716
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of vitrified-warmed cleavage-stage embryo hatching after in vitro laser-assisted zona pellucida thinning in patients

Abstract: Abstract. The aim of the present study was to determine whether the size of the zona pellucida (ZP) thinning area by laser-assisted hatching affected the potential development of vitrified-warmed embryos. A total of 196 vitrified-warmed cleavage-stage embryos (from 49 patients, four sister embryos per patient) were used in the study, i.e., four sister embryos from each patient were randomly assigned to four groups: A control group of embryos that were not zona-manipulated (zona intact, group A); one experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…A beneficial effect of LAH application on in vitro blastulation process has been implicated by abundant evidence that zona ablations by laser in cleavage embryos result in a better implantation potential and clinical pregnancy, especially for the cases of poor prognosis ( 9 , 10 ). And the direct evidence related to this benefit has been reported in our and other’s studies ( 11 , 12 ). All these findings encourage the addition of LAH operation during the extended culture process for untransferable cleavage embryos to promote the utilization of low-graded embryos, especially for the fragmented ones.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…A beneficial effect of LAH application on in vitro blastulation process has been implicated by abundant evidence that zona ablations by laser in cleavage embryos result in a better implantation potential and clinical pregnancy, especially for the cases of poor prognosis ( 9 , 10 ). And the direct evidence related to this benefit has been reported in our and other’s studies ( 11 , 12 ). All these findings encourage the addition of LAH operation during the extended culture process for untransferable cleavage embryos to promote the utilization of low-graded embryos, especially for the fragmented ones.…”
Section: Introductionsupporting
confidence: 81%
“…Another likely explanation for the advantage of LAHs relies on advanced escape from encapsule of zona and shorter coexistence of the developing embryos with the adverse environments. Indeed, a bulk of evidence have proven that both LAO and LAT be able to accelerate the process of hatching, and some considered that these methods can increase the blastocyst formation ( 11 , 12 , 14 , 40 ). In view of this, relieving the developing embryos from a deleterious circumstance caused by fragmentation might be the common pathway for the two LAHs, and explain the equal beneficial effect for LAO and LAT.…”
Section: Discussionmentioning
confidence: 99%
“…The rates were 71% in the nonintervention group and 51% in maximal ZP thinning group. 26 Oocyte from older women may be more vulnerable to the thermal damage of LAH, a recent study showed that ZP thickness linearly decreases with age and this may expose the blastomeres to higher temperatures. 14 Assisted hatching at the cleavage stage may expose the embryo to free radicals, toxins, and immune cells, causing DNA damage and impairs development to the blastocyst stage in utero.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this is that vitrification may impair hatching of the embryo. Theoretically, assisted hatching (AH) may facilitate the hatching process and subsequently increase the implantation rate [ 2 3 6 ]. Many authors have suggested that perforating or thinning the ZP of frozen-thawed embryos by AH facilitates embryonic implantation by making it easier for the embryo to exit the surrounding ZP [ 7 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first three methods require manual or motorized micromanipulators and skilled embryologists, and carry a risk of direct mechanical injury or toxicity. Research has shown LAH to be more effective, simpler, and faster than mechanical and chemical methods [ 6 ]. Non-contact laser systems using infrared wavelengths (1.4 µm) are commonly used in LAH today.…”
Section: Introductionmentioning
confidence: 99%